ANALISIS KUALIATAS KEPEMIMPINAN DALAM MENINGKATKAN PARTISIPASI AKTIF JAMAAH DI MASJID AL-MUHAJIRIN - Agustina, Agustina (Mushawwir Jurnal Manajemen Dakwah dan Filantropi Islam, 2024)
This research aims to analyze the quality of leadership in the context of increasing active congregational participation in mosques. By utilizing a qualitative approach, data was collected through in-depth interviews with mosque leaders and direct observation of mosque activities. The results of the analysis show that leadership qualities, which include a clear vision, effective communication skills, concern for the needs of the congregation, and the ability to build an inclusive community, have a positive impact on the active participation of the congregation. These findings provide valuable insight for the development of more effective leadership strategies in increasing the involvement and contribution of the congregation in mosque activities. This research aims to analyze the quality of leadership in the context of increasing the active participation of the congregation in the mosque. By utilizing a qualitative approach, data was collected through in-depth interviews with mosque leaders and direct observation of mosque activities. The results of the analysis show that leadership qualities, which include a clear vision, effective communication skills, concern for the needs of the congregation, and the ability to build an inclusive community, have a positive impact on the active participation of the congregation. These findings provide valuable insights for the development of more effective leadership strategies in increasing the involvement and contribution of congregants in mosque activities.